1997
DOI: 10.1002/hlca.19970800418
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Fe+‐Mediated [4+2] Cycloadditions in the Gas Phase

Abstract: (1 6.1V.97)The Fe+-mediated [4+2] cycloaddition of dienes with alkynes has been examined by four-sector ion-beam and ion cyclotron resonance mass spectrometry. Prospects and limitations of this reaction were evaluated by investigating several Me-substituted ligands. Me Substitution at C(2) and C(3) of the diene, i.e., 2-methylbuta-l,3-diene, 2,3-dimethylbuta-l,3-diene, hardly disturbs the cycloaddition. Similarly, variation of the alkyne by use of propyne and but-2-yne does not affect the [4+2] cycloaddition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Because it consists of multiple steps, the 1,3-C 4 H 6 + La­(C 2 H 2 ) reaction can only been called a nonconcerted [4 + 2] cycloaddition, not a traditional Diels–Alder reaction. Furthermore, unlike previously reported metal ion-mediated [4 + 2] cycloadditions with both diene and dienophile as initial reactants, the dienophile in this reaction is a metallacycle produced as an intermediate by the primary reaction.…”
Section: Results and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Because it consists of multiple steps, the 1,3-C 4 H 6 + La­(C 2 H 2 ) reaction can only been called a nonconcerted [4 + 2] cycloaddition, not a traditional Diels–Alder reaction. Furthermore, unlike previously reported metal ion-mediated [4 + 2] cycloadditions with both diene and dienophile as initial reactants, the dienophile in this reaction is a metallacycle produced as an intermediate by the primary reaction.…”
Section: Results and Discussionmentioning
confidence: 75%
“…Several mass spectrometric studies have reported transition metal ion M + (M = Cr, Mn, Fe, and Co)-mediated [4 + 2] cycloadditions of 1,3-butadiene with acetylene (or propyne) to yield 1,4-cyclohexadiene/M + , which subsequently dehydrogenates to produce benzene/M + as the major product. Without a dienophile, 1,3-butadiene reactions with metal ions (Fe + and W + ), , metal oxide cluster ions (V x O y + and Ta x O y + ), or neutral metal oxide clusters (VO 3 (V 2 O 5 ) n ) yielded association, dehydrogenation, or C–C bond cleavage products. In this work, we report spectroscopic characterization of the La atom reaction with 1,3-butadiene in a molecular beam source.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical study of organometallic ion chemistry provides important insights into catalytic systems and may allow the design of more selective and benign catalysts in the future. There are many examples of transition metal cations coordinating to organic substrates and promoting particular reaction pathways. For example, Fe + can promote the retrocyclization of norbornadiene (NBD) and norbornene (NBN) to form CpFeC 2 H 2 + and CpFeC 2 H 4 + , respectively …”
Section: Introductionmentioning
confidence: 99%